Navigating pitfalls and misinterpretations in the use of historical sources for Huemul (Hippocamelus bisulcus) conservation: A critique to Flueck et al. (2023) - Norma I. Díaz; Paulo Corti (Gayana)
In a recent article, Flueck et al. (2023) argue that the huemul (Hippocamelus bisulcus), an endemic South American deer species, historically occupied open habitats and islands, such as Tierra del Fuego, and that its decline was primarily due to indigenous hunting, commercial export of hides to Europe, habitat alteration by settlers, and the introduction of exotic species. We critically examine their use and interpretation of historical sources and highlight numerous methodological concerns that are similar to those we identified in a reply to a previous paper by the same authors (see Corti & Díaz 2023). We again emphasize the importance of rigorous quality control when using historical sources to inform current management of endangered species. This is crucial to prevent both, potential negative consequences resulting from proposed conservation efforts, and misguided future research efforts.